Mechanical and radiation shielding properties of flexible material based on natural rubber/ Bi2O3 composites - Sirilak Intom (2020)
© 2020 Elsevier Ltd The purpose of this investigation have been developed lead-free and flexible radiation shielding materials. Composites of natural rubber (NR) were prepared by incorporating bismuth oxide (Bi2O3) with various loading levels. The variation mechanical properties of the composite with different loading levels have been studied. The gamma ray shielding properties were measured with 137Cs (662 keV) source by Compton scattering technique. The X-ray shielding characterization were measured with high frequency digital radiography X-ray machine Shimadzu model RAD Speed Pro. The results show that addition of Bi2O3 into natural rubber enhances the modulus at 100% elongation, hardness and specific gravity of the composites, whereas tensile strength and elongation at break reduces. For gamma ray shielding properties, the experimental values of mass attenuation coefficients (μm), effective atomic number(Zeff), effective electron densities (Ne) and lead equivalent of the NR composites were found to increase with the increasing of Bi2O3 concentrations, while these value were decrease with the increasing of photon energy from 223 keV to 662 keV. The half value layer (HVL) values of all samples were decreased with the increasing of Bi2O3 concentrations. The NR of 150 phr Bi2O3 composites found to be the lowest HVL values in comparison with commercial window, serpentine, ordinary concrete and hemimatite-serpentine. For X-ray shielding properties, the linear attenuation coefficient (μ) and lead equivalent (dPb) were increased with increased Bi2O3 add in NR and show the decreasing of X-ray energies range.